Could a peer-led intervention increase uptake of chlamydia screening? A proof of principle pilot study. Issue 1 (1st August 2012) - Loaring, Jessica; Hickman, Matthew; Oliver, Isabel; Campbell, Rona; Trotter, Caroline; Macleod, John; Pye, Karl; Crichton, Joanna; Horner, Paddy
Abstract : Background: Uptake of the English National Chlamydia Screening Programme is lower than predicted necessary to result in a rapid fall in chlamydia prevalence. Peer-led approaches may increase screening uptake but their feasibility and acceptability to young people is not known. Methods: Focus groups and interviews with young women and men. Following interview, chlamydia postal kits were introduced to participants and their opinions on giving these out to their peers sought. Participants were asked for their views and experiences of discussing chlamydia screening and distributing kits to their friends 4–8 weeks after the focus group/interview. All kits returned to the laboratory over a 9-month period were recorded. Results: Six men (mean age 19 years) and six women (mean age 20 years) were recruited. In total 45 kits were distributed, 33 (73%) to female participants. 22 (67%) and 3 (25%) of kits given to females and males, respectively, were given to peers. Ten kits (22%; seven female, three male) all of which had been given out by females, were returned for testing. Participants generally felt positive about the idea of peer-led screening (PLS) using postal kits. However, embarrassment was a key theme, particularly among men. Generally women but not men were able to discuss PLS among their close friends. Both sexes felt PLS would be easier if kits were readily available in multiple sites, and chlamydia screening was more widely promoted. Conclusion: Female PLS but not male PLS was successful in recruiting peers to participate in chlamydia screening. An evaluation of the acceptability and cost-effectiveness of PLS is now indicated.